2023
DOI: 10.1111/jne.13263
|View full text |Cite
|
Sign up to set email alerts
|

CD68+ and CD8+ immune cells are associated with the growth pattern of somatotroph tumors and response to first generation somatostatin analogs

Abstract: Somatotropinomas are pituitary tumors with a heterogenous clinical behavior. The tumor microenvironment regulates the interaction between tumor cells and the host immune system, potentially modulating tumor behavior. Here, we aimed to investi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 78 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Earlier studies often determined the proportion of macrophages by employing pan markers such as CD68, CD163, or CD204. These indicators investigated possible relationships between treatment response and tumor progression [ 60 ]. M2 macrophage infiltration is the primary immunological landscape that the PitNETs subtypes exhibit [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies often determined the proportion of macrophages by employing pan markers such as CD68, CD163, or CD204. These indicators investigated possible relationships between treatment response and tumor progression [ 60 ]. M2 macrophage infiltration is the primary immunological landscape that the PitNETs subtypes exhibit [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the individual components of the TME, a tumor-infiltrating immune profile has been associated with poorer outcomes and recurrence in PitNETs [6]. Moreover, the identification of CD8+ T cells could predict the response to first-generation somatostatin analogs, regardless of tumor characteristics (hormone levels, size, and invasion) and patient age, as demonstrated by Chiloiro et al, where somatotropinomas with high levels of CD8+ and CD138+ lymphocytes responded to first-generation somatostatin analogs [45]. According to a recent study, anti-PD-L1 target therapy could act on those subgroups of PitNETs characterized by elevated Ki-67 and p53 values, with a higher percentage of tumorinfiltrating CD68+ macrophages and CD8+ TILs [46].…”
Section: Folliculo-stellate Cellsmentioning
confidence: 93%
“…Some authors reported increased CD8+ lymphocytes in invasive PitNETs [30,31]. Interestingly, CD8+ lymphocytes appear under-expressed in invasive or first-generation somatostatin analog-resistant somatotroph PitNETs [32,33]. In this respect, Marques P. et al showed that a low CD8:CD4 ratio is associated with increased tumor cell proliferation rather than an absolute decrease in CD8+ cells.…”
Section: Immune Cell Infiltratementioning
confidence: 99%